Laparoscopic surgery in a patient with foramen of Winslow hernia due to large uterine fibroids: a case report and literature review - Shusaku Honma; Takenori Itohara; Seigo Sha; Hirohiko Onoyama (Surgical Case Reports, 2021)
Abstract Background Foramen of Winslow hernia (FWH) is a rare but emergent condition caused by an increase in the foramen diameter, visceral mobility, and intra-abdominal pressure. To the best of our knowledge, this is the first study to report a case of FWH secondary to large uterine fibroids that was successfully treated with laparoscopic surgery. Case presentation A 52-year-old woman with large uterine fibroids was diagnosed with FWH. Because of the absence of signs of bowel ischemia and peritonitis, we performed an elective laparoscopic surgery through a 5-port system after bowel decompression using a long intestinal tube. Although foramen of Winslow closure was not performed, her postoperative course was uneventful. Conclusions Laparoscopic surgery for FWH is considered an extremely effective surgical treatment option because of its safety and efficacy in performing delicate procedures (such as adhesiolysis) with a good magnified field of view.